3D printing of complex origami assemblages for reconfigurable structures. Issue 39 (26th September 2018) - Zhao, Zeang; Kuang, Xiao; Wu, Jiangtao; Zhang, Qiang; Paulino, Glaucio H.; Qi, H. Jerry; Fang, Daining
Abstract : Digital light processing-based 3D printing is utilized to fabricate complex 3D reconfigurable origami structures. These origami assemblages can be directly created by one-step printing of the customized photocurable elastomer. Abstract : Origami engineering principles have recently been applied to a wide range of applications, including soft robots, stretchable electronics, and mechanical metamaterials. In order to achieve the 3D nature of engineered structures ( e.g. load-bearing capacity) and capture the desired kinematics ( e.g., foldability), many origami-inspired engineering designs are assembled from smaller parts and often require binding agents or additional elements for connection. Attempts at direct fabrication of 3D origami structures have been limited by available fabrication technologies and materials. Here, we propose a new method to directly 3D print origami assemblages (that mimic the behavior of their paper counterparts) with acceptable strength and load-bearing capacity for engineering applications. Our approach introduces hinge-panel elements, where the hinge regions are designed with finite thickness and length. The geometrical design of these hinge-panels, informed by both experimental and theoretical analysis, provides the desired mechanical behavior. In order to ensure foldability and repeatability, a novel photocurable elastomer system is developed and the designs are fabricated using digital light processing-based 3D printing technology. Various origami assemblages are produced to demonstrate the design flexibility and fabrication efficiency offered by our 3D printing method for origami structures with enhanced load bearing capacity and selective deformation modes.